A Mutant of Vibrio parahaemolyticus pirABVP (+) That Carries Binary Toxin Genes but Does Not Cause Acute Hepatopancreatic Necrosis Disease - Luis Fernando Aranguren Caro (Microorganisms, 2020)
Vibrio parahaemolyticus carrying binary toxin genes, pirAB, is one of the etiological agents causing acute hepatopancreatic necrosis disease (AHPND) in shrimp. This disease has emerged recently as a major threat to shrimp aquaculture worldwide. During a routine PCR screening of AHPND-causing V. parahaemolyticus strains, an isolate tested PCR positive for pirB (R13) and another isolate tested positive for both the pirA and pirB (R14) genes. To evaluate the pathogenicity of these isolates, specific pathogen-free (SPF) Penaeus vannamei were experimentally challenged. For both R13 and R14 isolates, the final survival rate was 100% at termination of the challenge, whereas the final survival with the AHPND-causing V. parahaemolyticus was 0%. The nucleotide sequence of the plasmid DNA carrying the binary toxin genes revealed that R13 contains a deletion of the entire pirA gene whereas R14 contains the entire coding regions of both pirA and pirB genes. However, R14 possesses an insertion upstream of the pirA gene. In R14, mRNA for both pirA and pirB genes could be detected but no cognate proteins. This shows that the genome of AHPND-causing V. parahaemolyticus is highly plastic and, therefore, detection of the pirA and pirB genes alone by DNA-PCR is insufficient as a diagnostic test for AHPND.